2022
DOI: 10.1186/s40959-022-00143-0
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic strategy for early detection of cardiotoxicity of doxorubicin: a prospective observational study

Abstract: Background Cancer chemotherapy using anthracyclines is associated with cardiotoxicity (CTX), and left ventricular ejection fraction (LVEF) analysis is not sensitive to early cardiotoxic changes. Left ventricular global longitudinal strain (LV GLS) monitoring helps screen subclinical CTX; however, the intervals at which it should be performed remain unclear. We aimed to evaluate the incidence of CTX in women with breast cancer and the associated factors and compare two echocardiographic monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Echocardiography, a non-invasive method for assessing heart function, is widely used by clinicians to detect abnormalities in cardiac function during chemotherapy. 37 Left ventricular function is evaluated through measurements of left ventricular ejection fraction (LVEF), left ventricular fractional shortening (LVFS), and heart rate. Several clinical and animal studies have reported the use of echocardiographic parameters to diagnose DOX-induced cardiotoxicity.…”
Section: Effect Of Ap On Echocardiography Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Echocardiography, a non-invasive method for assessing heart function, is widely used by clinicians to detect abnormalities in cardiac function during chemotherapy. 37 Left ventricular function is evaluated through measurements of left ventricular ejection fraction (LVEF), left ventricular fractional shortening (LVFS), and heart rate. Several clinical and animal studies have reported the use of echocardiographic parameters to diagnose DOX-induced cardiotoxicity.…”
Section: Effect Of Ap On Echocardiography Analysismentioning
confidence: 99%
“…Several clinical and animal studies have reported the use of echocardiographic parameters to diagnose DOX-induced cardiotoxicity. 37,38 Studies in rats have shown that DOX treatment leads to a decline in heart rate (beats/min), LVEF, and LVFS. 38,39 Similarly, this study observed a significant decrease in heart rate (244±17), LVEF (69.8±3%), and LVFS (29.5±2%) following DOX treatment.…”
Section: Effect Of Ap On Echocardiography Analysismentioning
confidence: 99%
“…Echocardiography (ECG) can be utilized to display cardiac anatomical structure and hemodynamics changes and assess cardiac functions. The main monitoring and assessment indicators for cardiotoxicity are ventricular diastolic and systolic functions, especially left ventricular ejection fraction (LVEF) [9]. According to relevant research, routine ECG has some application values in the monitoring of cardiotoxicity after ANTH chemotherapy [10].…”
Section: Introductionmentioning
confidence: 99%